Can anyone help me figure this out? If f(7)=6 , f ' (7)=9 , g(7)=10 , and g ' (7)=7 then: (f+g) ' (7) = (fg) ' (7) = thanks
Follow Math Help Forum on Facebook and Google+
Hello, Originally Posted by coldfire Can anyone help me figure this out? If f(7)=6 , f ' (7)=9 , g(7)=10 , and g ' (7)=7 then: (f+g) ' (7) = (fg) ' (7) = thanks Using basic rule of differentiation, $\displaystyle (f+g)'(x)=f'(x)+g'(x)$ Using multiplication rule : $\displaystyle (fg)'(x)=f'(x)g(x)+f(x)g'(x)$ .... !
ahhh, so simple.. I forgot (fg)' = f'(x)g(x) + g'(x)f(x) thanks
View Tag Cloud